2019
DOI: 10.1016/j.eja.2019.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Foliar N application at anthesis alters grain protein composition and enhances baking quality in winter wheat only under a low N fertiliser regimen

Abstract: Wheat is the second biggest staple crop worldwide and is mainly consumed in the form of baked goods, requiring a specific flour quality. Grain protein concentration (GPC) is an underpinning parameter for baking quality and therefore strongly influences the value of wheat. It is a common strategy to increase GPC by combining high protein varieties with the application of a late dose of nitrogen. However, the late use of N fertilisers can cause environmental problems, such as nitrate leaching and gaseous losses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Thus, high protein content did not consequently lead to a better ratio of GLIA/GLUT and a high amount of glutenins. These findings are in accordance with the literature [21,22,23,24].…”
Section: Resultssupporting
confidence: 94%
“…Thus, high protein content did not consequently lead to a better ratio of GLIA/GLUT and a high amount of glutenins. These findings are in accordance with the literature [21,22,23,24].…”
Section: Resultssupporting
confidence: 94%
“…Similar to our results, other biostimulants obtained from marine, fungal, or protein hydrolysates have not been shown to change the protein content in wheat (Popko et al, 2018;Pichereaux et al, 2019). However, none of the treatments from our work resulted in a protein content below the level required by the industry (11.5%) even though this is not the best criterion to ensure baking quality (Rossmann et al, 2019).…”
Section: Protein Content and Qualitysupporting
confidence: 85%
“…Foliar application of Glutacetine R with N fertilizer at heading did not significantly affect the grain N concentration (Figure 2) but impacted the quantities of 11 proteins relative to the control (Figure 5). As suggested by Rossmann et al (2019), these changes in the grain proteome could have been due to the foliar application of N fertilizers at anthesis and might enhance baking quality. Indeed, the same authors showed that foliar N application increased HMW glutenin while decreasing LMW glutenin and α-/β-/γ-gliadins.…”
Section: Protein Content and Qualitymentioning
confidence: 94%
“…The composition and functionality of storage proteins have been significantly affected by growing season and genotype, while the effect of N fertilization level was rather small (Table S2) [50] as also resulted by PCA analysis. Several studies reported an increase in the proportions of the monomeric gliadins with increasing N availability [26,27].…”
Section: Discussionmentioning
confidence: 85%